IMPLEMENTASI KEBIJAKAN KOTA LAYAK ANAK DI KABUPATEN NGANJUK - Putri Ambar Wanti Putri; Sri Wibawani (Halu Oleo University, 2024)
This research aims to describe the implementation of the Child Friendly City Policy in Nganjuk Regency using Edward III's implementation theory with four variables which include communication, resources, disposition and bureaucratic structure. This research is descriptive research with a qualitative approach with data collection techniques through observation, interviews and documentation. The research results show that the communication variable with the sub-focus of transmission, clarity and consistency is not optimal because the communication carried out is still not comprehensive enough for agencies so there are agencies that are not aware of the policy. In the resource variable with the sub-focus of staff, information, authority and facilities, it shows that it has been maximized, proven by the existence of human resources who have the ability and knowledge related to the policy so that they can carry out their duties and there are regulatory guidelines and technical instructions as well as physical facilities that can support implementation. that policy. The disposition variable with the sub-focus of cognition, direction and response from implementers, and intensity of response has been carried out well as seen from employees who understand related policies and carry out various policy-supporting programs with full responsibility. The final variable, namely the bureaucratic structure, has not been implemented optimally because there is no clear bureaucratic structure.